CEO Education, Tenure, and the Speed of Capital Structure Adjustment: The Moderating Role of Political Connections: JEL Classification: G32, G34, M12, P16, O16 - Rudy Candra; Arif Budi Satrio; Hartono (Newinera Publisher, 2026)
This study investigates how managerial and institutional factors influence the firm-level speed of capital structure adjustment (SOA). While prior research on dynamic capital structure largely estimates aggregate adjustment speeds, limited attention has been given to granular SOA measured at the firm-year level and its relationship with managerial decision-making and institutional context. Using panel data from 71 non-financial firms included in the Kompas100 Indeks, representing the 100 largest and most liquid companies on the Indonesia Stock Exchange (IDX), over the period 2019-2024, this study examines how CEO education, CEO tenure, and political connections affect firms’ leverage adjustment behavior. The analysis employs panel regression models to estimate firm-level SOA and evaluate the direct and moderating effects of managerial and institutional variables. The results show that CEO education significantly accelerates leverage adjustment, indicating that firms led by more highly educated executives adjust their capital structures toward target levels more quickly. In contrast, CEO tenure does not show a significant effect on SOA. The findings also reveal that political connections slow leverage adjustment but strengthen the positive influence of CEO education on SOA, suggesting that managerial capability becomes more effective when supported by institutional access. These findings highlight that capital structure adjustment is shaped by the interaction between managerial decision-making and institutional networks, rather than by managerial characteristics alone.